IMPLEMENTASI KEBIJAKAN PENDIDIKAN KINERJA GURU DALAM MENINGKATKAN PRESTASI SISWA DI MI ASSEGAF PALEMBANG - Ida Suryani (Universitas Negeri Medan, 2021)
Abstract: Teachers have a quite dominant influence on the quality of learning in the classroom even as the provider of education in schools. The most dominant teacher factor influencing the quality of learning is teacher performance. Performance is the result of work that can be approved by a person or group of people in an organization within a framework that is in accordance with the objectives of the law. Teacher competence is an embodiment of teacher competence that is equipped with the ability and motivation to complete tasks and motivation for development. Teacher performance is a dominant factor in determining the quality of learning. Hoping that teachers involved in learning activities have a good increase, will be able to improve student achievement, which in turn improves the quality of learning. Teacher performance that is enhanced against student achievement is teacher performance in the classroom. This research was conducted to see how the teacher planning in the process, teaching and learning process and the implementation of the learning process and teaching and learning outcomes. The study used a qualitative descriptive study with the subject of the teacher council that taught at SMA Negeri 2 Palembang. The techniques used in data collection consist of interviews, observation and documentation studies. The implementation of the teaching and learning process must be carried out in accordance with the learning plan.Keywords: Teacher Performance, Learning Quality, Student Achievement.Abstrak: Guru mempunyai pengaruh yang cukup dominan terhadap kualitas pembelajaran dikelas bahkan sebagai penyelenggara pendidikan di sekolah. Faktor guru yang paling dominan mempengaruhi kualitas pembelajaran adalah kinerja guru. Kinerja adalah sebagai hasil kerja yang dapat dicapai oleh seseorang atau sekelompok orang dalam suatu organisasi dalam rangka upaya mencapai tujuan secara legal. kinerja guru merupakan perwujudan kompetensi guru yang mencakup kemampuan dan motivasi untuk menyelesaikan tugas dan motivasi untuk berkembang. Kinerja guru merupakan faktor yang dominan dalam menentukan kualitas pembelajaran. Artinya kalau guru yang terlibat dalam kegiatan pembelajaran mempunyai kinerja yang bagus, akan mampu meningkatkan prestasi siswa yang pada akhirnya meningkatkan kualitas pembelajaran . kinerja guru yang berpengaruh terhadap prestasi siswa adalah kinerja guru dalam kelas. Penelitian ini di lakukan untuk melihat bagaimana kinerja guru dalam perencanaan, pelaksanaan proses belajar mengajar serta pelaksanaan evaluasi proses dan hasil belajar mengajar. Penelitian menggunakan pendekatan deskriptif kualitatif dengan subjek penelitian adalah seluruh dewan guru yang mengajar pada SMA Negeri 2 Kota Palembang. Adapun teknik yang di gunakan dalam mengumpulkan data berupa teknik wawancara, observasi dan studi dokumentasi. Pelaksanaan proses belajar mengajar harus di laksanakan sesuai dengan perencanaan pembelajaran.Kata kunci: Kinerja Guru, Kualitas Pembelajaran, Prestasi Siswa